5R-based character strengthening model to support halal aquaculture industry practitioners through good water quality management and safe machinery operation - Achmad Widodo, Syukri Fathudin; Muflih, Betania Kartika; Nuryanto, Apri; Tri Harjanto, Chrisna; Razali, Mohamad Afiq; Al Giffari, Haekal Adha (Zibeline International, 2021)
This research aims to design 5R character-based halal industry players (Ringkas, Rapi, Resik, Rawat, Rajin) or 5S (Sort, Set in Order, Shine, Standardize, Sustain), as well as their debriefing for UNY and IIUM students in supporting the Halal industry related to Good Aquaculture Practices. This area has been selected, due to some factors. The first is the occurrence of several cases of aquaculture products that changed status from being permissible to become impermissible due to the external factors, for example, the fact that the water quality is bad and contaminated with harmful chemical substances. Water quality is the most important factor affecting fish health and performance in aquaculture production system. Secondly the fish nutrition and feeding are mixed with unclean and filthy ingredients. Thirdly, it is exposed to the risk of contamination from the equipment, which eventually affects halal integrity. Halal products cannot be prepared, processed, or manufactured using equipment that is contaminated with non-halal substances (unclean defined by Shariah). Contamination can be caused by equipment that is contaminated or used together with non-halal products. Therefore, equipment and machinery used in the halal aquaculture industry play a very important role to ensure halal integrity. This paper uses a library and literature review approach. It is expected that with the arrangement of 5R or 5S-based character strengthening design, the operators of Aquaculture Industry may preserve Halal Supply Chain.